Inkjet-based micromanufacturing - Korvink, J. G. (Jan G.); Smith, Patrick J. (Mechanical engineer); Shin, Dong-Youn (Advanced micro & nanosystems ;, 2012)
Inkjet-based Micromanufacturing Inkjet technology goes way beyond putting ink on paper: it enables simpler, faster and more reliable manufacturing processes in the fields of micro- and nanotechnology. Modern inkjet heads are per se precision instruments that deposit droplets of fluids on a variety of surfaces in programmable, repeating patterns, allowing, after suitable modifications and adaptations, the manufacturing of devices such as thin-film transistors, polymer-based displays and photovoltaic elements. Moreover, inkjet technology facilitates the large-scale production of flexible RFID tr.